Google Guice: Agile Lightweight Dependency Injection Framework\ - Vanbrabant, Robbie (Apress, 2012)
created Guice in the midst of one of the biggest projects of my career. When you have hundreds of engineers touching millions of lines of code, you come to appreciate the benefits of static type checking. Static types aren’t just about compiler errors. In fact, I rarely see Java compiler errors nowadays. Thanks to all that great, formalized Java type information, my IDE helps me write correct code in the first place. Writing your application in a nearly 100 percent type safe manner, like Guice enables and Robbie advocates in this book, opens the door to a new level of maintainability. You can effortlessly navigate unfamiliar code, jumping from interfaces to their implementation and from methods to their callers. As you master your Java tools, you realize that deceptively simple atomic refactorings combine to form molecular tools, which you can reliably apply to companywide swaths of code, accomplishing refactorings you’d never even consider trying by hand. In the long run, it’s much cheaper to ward off bit rot through heavy reuse and constant refactoring than by nuking the world with a rewrite every couple years.